2016
DOI: 10.1007/s00262-016-1856-z
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint blockade with concurrent electrochemotherapy in advanced melanoma: a retrospective multicenter analysis

Abstract: Growing evidence suggests that concurrent loco-regional and systemic treatment modalities may lead to synergistic anti-tumor effects in advanced melanoma. In this retrospective multicenter study, we evaluate the use of electrochemotherapy (ECT) combined with ipilimumab or PD-1 inhibition. We investigated patients with unresectable or metastatic melanoma who received the combination of ECT and immune checkpoint blockade for distant or cutaneous metastases within 4 weeks. Clinical and laboratory data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 25 publications
1
87
0
3
Order By: Relevance
“…Another retrospective study by Heppt et al . evaluated the use of ECT with a CTLA‐4 inhibitor (ipilimumab) versus ECT with PD‐1 inhibitors (pembrolizumab or nivolumab) in the treatment of unresectable or metastatic melanoma . A total of 28 patients received ECT with ipilimumab, while a total of five patients received ECT with PD‐1 inhibitors (pembrolizumab n = 3, nivolumab n = 2) .…”
Section: Electrochemotherapy In Combination With Immunotherapy In Thementioning
confidence: 94%
See 1 more Smart Citation
“…Another retrospective study by Heppt et al . evaluated the use of ECT with a CTLA‐4 inhibitor (ipilimumab) versus ECT with PD‐1 inhibitors (pembrolizumab or nivolumab) in the treatment of unresectable or metastatic melanoma . A total of 28 patients received ECT with ipilimumab, while a total of five patients received ECT with PD‐1 inhibitors (pembrolizumab n = 3, nivolumab n = 2) .…”
Section: Electrochemotherapy In Combination With Immunotherapy In Thementioning
confidence: 94%
“…However, this immune response does not appear to be robust enough to cause regression of untreated distant tumor nodules . This has led to studies investigating the use of ECT in combination with immunostimulating agents, first in animal models and more recently in humans, to determine if this therapeutic combination could augment the ECT‐induced immunological response and lead to a systemic antitumor response …”
Section: Electrochemotherapy In Combination With Immunotherapy In Thementioning
confidence: 99%
“…Ding et al reported that combined treatment of anti-PD-1 mAb and low-dose chemotherapeutic drugs (cisplatin or paclitaxel) increased anti-cancer efficacy achieved a long-term curative effect (Ding et al, 2014). Additional studies have suggested that immune checkpoint inhibitors, combined with electrochemotherapy, enhanced antitumor benefit in advanced melanoma (Heppt et al, 2016; Hutchinson, 2016). After investigating the impact of radiotherapy (RT), chemotherapy (CT), and RCT on PD-L1 surface expression on different tumor cells, and treating with cells with different chemoradiation therapies, Derer et al found increased PD-L1 expression in certain Melanoma and glioblastoma cells (Derer et al, 2016).…”
Section: Combination Administrationmentioning
confidence: 99%
“…Az ECT ipilimumabbal tör-ténő kombinációját multicentrikus retrospektív vizsgálatban elemezték. 28 beteg ipilimumab kezelést, 5 beteg PD1-gát-ló kezelést (nivolumab: 3 beteg, pembrolizumab: 2 beteg) kapott az ECT mellett (32). Az utánkövetési idő median érté-ke 9 hónap volt.…”
Section: Lokoregionális Kezelések éS Immunonkológiai Gyógysze-rek Komunclassified